A antípoda da civilização - Miranda, José Augusto Ribas (Diálogos Latinoamericanos, 2013)
Republic and Anarchy. Monarchy and Civilization. These ideas were applicants in the speeches of the conservative senators and deputies of the Brazilian Empire. Located in a mostly republican American scene, the Brazilian Empire had conservative elite that sought to put the monarchy, inextricably linked to the European tradition, as a light among the political instability of the Hispanic republics. An important element that sought to outline the actions and operation of the Brazilian monarchy, a “civilizational project” in America, was the Ensaio sobre o Direito Administrativo, the 1862 work of Paulino José Soares de Souza, Viscount of Uruguai. Through the analysis of this work, this article seeks to trace the negative image the republican system had for the imperial conservative elite, greatly affected by the Hispanic examples. It also looks to present the opinions of Viscount of Uruguai and his colleagues, in which the monarchy was conceived as a guarantor of the constitutional stability; the constitutional stability as guarantor of the political stability and the political stability as key to achieving the highest stage of civilization.